The Use of Antidepressants in Depressed Patients in the National Institute of Mental Health - Bach Mai Hospital - Bach, Nguyen Xuan; Hai, Nguyen Thanh; Ly, Nguyen Huong; Tuan, Nguyen Van (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 34 No 1, 2018)
Abstract: According to the WHO (World Health Organization), unipolar depressive disorders were ranked as the third leading cause of the Global Burden of Disease in 2004 and are expected to move into the first place by 2030. Methods: Research conducted on 65 patients at the National Institute of Mental Health to examine the use of drugs, their side effects, drug interactions and effectiveness of treatment in these patients. Results: The study results showed that Sertraline was the most widely used antidepressant (39.5%), followed by Mirtazapine (38.3%). Adverse events in the most common symptoms were resulted from cholinergics. There were 12 patients (18.5%) recorded experiencing adverse events on weight. The rate of remission HAM-D 17 scale scores after treatment was 66.2 ± 13.8%. Conclusions: New antidepressants were commonly used and had effects among the unipolar depressive patients in Vietnam. Clinicians should pay attention to such side effects as cholinergic adverse events and weight gain among patients. Keywords Antidepressant, depression, side effects, drug use References [1] American Psychiatric Association, Practice guiline for the treatment of patients with major depressive disorder, Third Edition (2010). [2] Duval, Lebowitz, Macher, “Treatments in Depression”, Dialogues in Clinical Neuroscience, 8 (2006) 191. [3] Raj Rasasingham, “Efficacy and Safety of Antipsychotics for the Treatment of Major Depressive Disorder in Adolescents and Adults: Current Issues and Clinical Perspective”, Open Journal of Psychiatry, 4 (2014) 182. [4] Kessler RC, McGonagle KA, Swartz M, Blazer DG, Nelson CB. “Sex and depression in the National Comorbidity Survey I: Lifetime prevalence, chronicity and recurrence”, Journal of Affectice Disorders, 29 (1993) 85.